Ten-Year Secular Changes in Selected Health and Fitness Parameters of 10-11 Years Old Swansea School Children – 2003-2013 - Kelly Mackintosh (Advances in Obesity, Weight Management & Control, 2015)
Purpose: The aim of this study was to highlight the secular changes in selected health and fitness measures (body mass index, prevalence of overweight and obesity and grip strength) in 10-11 year old Swansea school children, using data obtained in 2003 and 2013.Methods: Stature, body mass and grip strength data were collected for 512 participants (n= 230 boys, n= 282 girls) in 2003 during a Crucial CrewDay and for 414 participants (n= 198 boys, n= 216 girls) in 2013 during the Swan-Linx programme. BMIs were calculated from this data and used to calculate BMI standard deviation scores. A two-way ANOVA was conducted to examine if there was a statistically significant difference in BMI z-score by gender and year of testing. A two-way ANCOVA was used to investigate if there were differences on grip strength by gender and year of testing, with BMI z-score as a covariate.Results: BMI z-scores decreased significantly (p = 0.001) between 2003 and 2013 for both boys (0.80 to 0.40) and girls (0.58 to 0.41). Prevalence of overweight and obesity decreased for both boys and girls from 31.7% to 23.8% and 33.8% to 29.7%, respectively. After BMI z-scores adjustment, grip strength decreased significantly for boys (18.43kg to 16.88kg, p < 0.001), but not for girls (16.53kg to 16.59kg).Conclusion: The study shows promising results in terms of BMI z-scores and prevalence of overweight and obesity. However, the prevalence of overweight and obesity recorded in 2013 is still high, therefore further decreases in prevalence should continue to be an aim. The study also shows that muscular strength, in boys in particular, should be a focus for future interventions regarding physical fitness, in addition to an area for further investigation.